ROLE OF COMPUTED TOMOGRAPHY OF THE SECOND CERVICAL VERTEBRA IN SEX IDENTIFICATION AMONG EGYPTIANS (Journal of Forensic Medicine & Toxicology, 2023)
Sex identification using incomplete skeleton of single bones is important in forensic investigation. The second cervical vertebra was proved to have a role in sex identification. In the current study, one hundred and twenty-two Egyptians were included; half of them were males and the other half were females (with age range between 20 to 65 years). For all subjects, after informed consent, Computed tomographies of the neck were done and thirteen linear measurements from the 2nd cervical vertebra were used for sex identification. The study showed that the 2nd cervical vertebra can be useful as a sex indicator at an accuracy of 89.3% and can be added to sex identification tools in forensic investigations.
Keywords: Sex; Identification; Second cervical vertebra; Egyptians; vertebra; Egyptians